Xenopus laevis as a Model Organism for the Study of Spinal Cord Formation, Development, Function and Regeneration - Borodinsky, Laura N. (Frontiers in Neural Circuits, 2017)
The spinal cord is the first central nervous system structure to develop during vertebrate embryogenesis, underscoring its importance to the organism. Because of its early formation, accessibility to the developing spinal cord in amniotes is challenging, often invasive and the experimental approaches amenable to model systems like mammals are limited. In contrast, amphibians, in general and the African-clawed frog Xenopus laevis, in particular, offer model systems in which the formation of the spinal cord, the differentiation of spinal neurons and glia and the establishment of spinal neuron and neuromuscular synapses can be easily investigated with minimal perturbations to the whole organism. The significant advances on gene editing and microscopy along with the recent completion of the Xenopus laevis genome sequencing have reinvigorated the use of this classic model species to elucidate the mechanisms of spinal cord formation, development, function and regeneration.